Structure design and stability analysis of free-diving sediment trap - Rui WANG; Caoyang YU; Yiming ZHONG; Lian LIAN (Zhongguo Jianchuan Yanjiu, 2023)
ObjectivesThis study focuses on how the sampling efficiency of a free-diving sediment trap (FST) is affected by its body posture, and uses quantitative analysis to describe the changes of the center of gravity and attitude angles. MethodsAn FST is designed which consists of a sampling module and a buoyancy control system. A 3D model of the FST is built using SolidWorks. Kinematic analysis is completed using Matlab, and the offset of the center of gravity at each moment in the whole working cycle is obtained by simulation. The principle of moments is used to derive its attitude changes caused by the offset of the center of gravity. The influence of the attitude changes on the effective collection area is then quantitatively analyzed using projective transformation. ResultsThe result shows that the offset of the center of gravity is limited to a circle with the origin of the body-fixed coordinate system as the center and a radius of \begin{document}$ 8 × {10^{ - 3}}\;{\text{m}} $\end{document}. It is seen that the domains of x and y are \begin{document}${x_{\text{g}}} \in ( - 6 × {10^{ - 3}}\;{\text{m}},{\text{ }}3 × {10^{ - 3}}\;{\text{m}})$\end{document}, \begin{document}${y_{\text{g}}} \in ( - 1 × {10^{ - 3}}\;{\text{m}},{\text{ }}7 × {10^{ - 3}}\;{\text{m}})$\end{document}, and the domains of the attitude angles are \begin{document}$ θ \in ( - 1.5^° ,{\text{ }}16.6^° ) $\end{document} and \begin{document}$φ \in ( - {2.6^ ° },{16.8^ ° })$\end{document}. When \begin{document}$θ = 14.7^° {\text{ and }}φ {\text{ = 13}}^°$\end{document}, the effective collection area is reduced to 94.27% of the original value. Compared with the 100% effective collection area, it takes 1.06 times the original collection time to collect the same volume of sinking particles. ConclusionsThe results of this study can provide useful references for FST stability analysis and buoyancy regulation system design.